Characteristics of salivary microbiota in children with obstructive sleep apnea: A prospective study with polysomnography - Huang, Xin; Chen, Xuehui; Gong, Xu; Xu, Ying; Xu, Zhifei; Gao, Xuemei (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: The present study aimed to investigate the characteristics of salivary microbiota of children with obstructive sleep apnea (OSA) and to assess longitudinal alterations in salivary microbiota before and after adenotonsillectomy. Methods: A set of cross-sectional samples consisted of 36 OSA children (17 boys and 19 girls, 7.47 ± 2.24 years old) and 22 controls (9 boys and 13 girls, 7.55 ± 2.48 years old) were included in the study, among which 8 OSA children (5 boys and 3 girls, 8.8 ± 2.0 years old) who underwent treatment of adenotonsillectomy were followed up after one year. Saliva samples were collected, and microbial profiles were analyzed by bioinformatics analysis based on 16S rRNA sequencing. Results: In cross-sectional samples, OSA group had higher α-diversity as estimated by Chao1, Shannon, Simpson, Pielou_e and observed species compared with control group (p < 0.05). βdiversity based on Bray‐Curtis dissimilarities (p = 0.004) and Jaccard distances (p = 0.001) revealed a significant separation between OSA group and control group. Nested cross-validated random forest classifier identified 10 most important genera (Lactobacillus, Escherichia, Bifidobacterium, Capnocytophaga, Bacteroidetes_[G-7], Parvimonas, Bacteroides, Klebsiella, Lautropia, and Prevotella) that could differentiate OSA children from controls with an area under the curve (AUC) of 0.94. Linear discriminant analysis effect size (LEfSe) analysis revealed a significantly higher abundance of genera such as Prevotella (p = 0.027), Actinomyces (p = 0.015), Bifidobacterium (p < 0.001), Escherichia (p < 0.001) and Lactobacillus (p < 0.001) in OSA group, among which Prevotella was further corroborated in longitudinal samples. Prevotella sp_HMT_396 was found to be significantly enriched in OSA group (p = 0.02) with significantly higher levels as OSA severity increased (p = 0.014), and it had lower abundance in post-treatment group (p = 0.003) with a decline in each OSA children one year after adenotonsillectomy. Conclusions: A significant higher microbial diversity and a significant difference in microbial composition and abundance were identified in salivary microbiota of OSA children compared with controls. Meanwhile, some characteristic genera (Prevotella, Actinomyces, Lactobacillus, Escherichia, Bifidobacterium) were found in OSA children, among which the relationship between Prevotella spp. and OSA is worth further studies.